RECENT ADVANCES IN FEMALE PHYSIOLOGY AND PATHOLOGY - NINA A. Barbarash; DMITRY YU. Kuvshinov (Фундаментальная и клиническая медицина)
Here we review the recent data on female psychophysiology as well as gender-related risk factors and features of various diseases. We further suggest a gender approach for teaching the new generations and for analyzing the emotional factors. Strikingly, females generally have a higher consumption of fresh vegetables and fruits and lower consumption of salt compared to males; however, abdominal obesity is more prevalent in females than in males, particularly in those with diabetes mellitus. Passive smoking is also more harmful for females in comparison with males; this should be of particular importance due to increasing number and proportion of female smokers. During the last four decades, cardiovascular mortality reduced in males but not in females. Therefore, society should focus the attention on the struggle with gender blindness.